STRUKTUR PASAR, KEKUATAN PASAR RELATIF, DAN EFISIENSI TERHADAP PROFITABILITAS PERUSAHAAN ASURANSI UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Geovanni K. O. Robert; Jakaria , (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
This thesis discusses the influence of market structure, market power relative, and the efficiency of the company on Profitability general insurance company. The independent variables used include CR16 as a proxy of the market structure, market share as a proxy of the relative market power, and CRS as an efficiency measure. The method used in this thesis is the method of panel data regression method. This study aims to determine which is the most influential variable on Profitability general insurance company in Indonesia. Results showed that variable relative market power (market share) has the most impact on Profitability general insurance company. Then, simultaneously three independent variables significant effect on Profitability. Based on the coefficient of integration test results, the ability of independent variables in the model to explain the dependent variable changes is amounted to 18.07 %.